First-year university students' willingness to communicate in English language inside and outside the classroom: An investigative mixed method - Almziad, Amal Abdullah (Edelweiss Applied Science and Technology, 2025)
The study aimed to investigate the viewpoints of first-year students at Majmaah University, Saudi Arabia, about their willingness to engage in communication in the English language, both inside and outside the classroom. A mixed-methods research approach was used, combining qualitative and quantitative data collection techniques. The study was conducted at Majmaah University in Saudi Arabia over 8 weeks, involving 30 first-year English major students (20 female and 10 male). Data collection included: questionnaires measuring WTC in and outside the classroom, self-reflective reports analyzing students' speaking challenges, semi-structured interviews with selected participants to explore their perceptions of WTC, and classroom observations to understand communication patterns. Quantitative data were analyzed using SPSS, employing descriptive statistics, t-tests, and ANOVA. Qualitative data were subjected to thematic analysis to identify key factors influencing WTC. The current investigation revealed that the majority of students had a greater inclination to engage in verbal communication inside and outside the classroom setting. Simultaneously, the absence of an English-speaking environment made a dynamic atmosphere crucial for WTC outside of the classroom. Some factors that affected the foreign language anxiety qualitative data include the level of the expected interlocutor, the relationship with the voice, and the members of the language class together with the student's supportive friends.